2020
DOI: 10.1007/s00266-020-01693-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Depressor Nasi Septi Muscle in Nasal Air Flow

Abstract: Background Musculus depressor septi nasi and its tendon, the dermocartilaginous ligament, play an important role in external nasal valve and nasal respiration. If the ligament is cut during septorhinoplasty operations, nasal functions of the nose and facial expressions are affected. Therefore, the aim of this study was to investigate the role of M. depressor septi nasi in nasal respiration at open rhinoplasty operations using rhinomanometry and electromyography. Methods The study included 29 patients who had o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Some considered the disruption of the DSNm as a sacrifice of the function in favor of nasal aesthetics, as the NTDs’ main function is to dilate the nostrils that facilitate nasal air inflow. 6 Theoretically, the disruption of the NTDs may cause postrhinoplasty functional disturbances, and this theory should be supported with more rhinometric studies in the future.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some considered the disruption of the DSNm as a sacrifice of the function in favor of nasal aesthetics, as the NTDs’ main function is to dilate the nostrils that facilitate nasal air inflow. 6 Theoretically, the disruption of the NTDs may cause postrhinoplasty functional disturbances, and this theory should be supported with more rhinometric studies in the future.…”
Section: Discussionmentioning
confidence: 95%
“… 5 Normally, the DSNm acts to drop the nasal tip caudally, widen the nostril area, and facilitate nasal air inflow. 6 The DSNm is a paired muscle that originates from the maxilla‚ just above the related central incisors. The midportion fibers of the DSNm insert into the anterior nasal spine (ANS), footplates of the medial crura, and then to the membranous septum.…”
Section: Introductionmentioning
confidence: 99%
“…After mucosal decongestion, the FRIED test revealed that the difference between inspiratory and expiratory flows at a pressure difference of 100 Pa exceeded 9 ml/s in 58% of cases (Table 2), suggesting passive or active movement of the lateral nasal wall in many patients during RMN. [37][38][39][40]…”
Section: Rhinomanometrymentioning
confidence: 99%